Serum HER2 Is a Potential Surrogate for Tissue HER2 Status in Gastric Cancer: A Systematic Review and Meta-Analysis. - Kecheng Zhang; Jianxin Cui; Hongqing Xi; Shibo Bian; Liangang Ma; Weisong Shen; Jiyang Li; Ning Wang; Bo Wei; Lin Chen (PLoS ONE, 2015)
Determining the expression level of human epidermal growth factor receptor 2 (HER2) in tumor tissue is of great importance for personalized therapy in gastric cancer. Although several studies have investigated whether serum HER2 can serve as a surrogate for tissue HER2 status, results have been inconsistent. We therefore performed a meta-analysis of published clinical studies in an attempt to address this problem. PubMed, Embase, Web of Science, the Cochrane Library and Science Direct were queried for eligible studies that could provide sufficient data to construct 2 × 2 contingency tables. The quality of the studies included in the meta-analysis was assessed in accordance with the revised Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) criteria. The pooled sensitivity, specificity and diagnostic odds ratio (DOR) were calculated for the eligible studies. The summary receiver operating characteristic (SROC) curve was constructed and the area under the SROC (AUSROC) was used to evaluate overall diagnostic performance. Eight studies comprising a total of 1170 participants were included in our meta-analysis. The pooled sensitivity, specificity and DOR were 0.39 (95% CI: 0.21-0.61), 0.98 (95% CI: 0.87-1.00), and 27 (95% CI: 9-81), respectively. The AUSROC was 0.77 (95% CI: 0.73-0.80) and Deeks funnel plot suggested the absence of publication bias (p = 0.91). Meta-regression analysis indicated that threshold effect was the main source of heterogeneity. Assays for evaluating serum HER2 levels are highly specific and demonstrate moderate diagnostic performance for HER2 tissue status in gastric cancer.